Bioinspired elastic piezoelectric composites for high-performance mechanical energy harvesting. Issue 30 (2nd July 2018) - Zhang, Yong; Jeong, Chang Kyu; Yang, Tiannan; Sun, Huajun; Chen, Long-Qing; Zhang, Shujun; Chen, Wen; Wang, Qing
Abstract : A bioinspired architecture of piezoceramics is developed for new composite structures overcoming the major limitations of the current piezoelectric polymer composites. Abstract : We report the sea sponge-inspired design and preparation of piezoelectric composite generators (PCGs) based on a three-dimensional electroceramic skeleton. The remarkable improvements in the piezopotential of the bioinspired structure have been theoretically analyzed using numerical simulations based on a phase-field simulation. The open-circuit voltage, short-circuit current density and instantaneous power density of the bioinspired PCG reach up to ∼25 V, ∼550 nA cm −2 and ∼2.6 μW cm −2, respectively, corresponding to about 16 times higher power than that of conventional particle based piezoelectric polymer composites. Moreover, the bioinspired PCG displays 30 times higher strain–voltage efficiency under stretching than the state-of-the-art performance of the flexible piezoelectric energy harvesters reported so far.